2011
DOI: 10.1161/strokeaha.110.603902
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Susceptibility to Infarct Growth in Women

Abstract: Background and Purpose-It is not known if there is a relationship between gender and tissue outcome in human ischemic stroke. We sought to identify whether the proportion of initially ischemic to eventually infarcted tissue was different between men and women with ischemic stroke. Methods-We studied 141 consecutive patients with acute ischemic stroke who had a baseline MRI obtained within 12 hours of symptom onset, a follow-up imaging on Day 4 or later, and diffusion-weighted imaging/mean transmit time mismatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…Previous work using perfusion–diffusion MRI, within 12 h of stroke onset, has suggested that age is a predictor of loss of penumbral tissue to the final infarction 8 9. Although in these studies the penumbra was defined visually without the use of quantitative thresholds, which may be prone to errors,31 our data point to a differential early response that may progress along the distinct trajectory they illustrate.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous work using perfusion–diffusion MRI, within 12 h of stroke onset, has suggested that age is a predictor of loss of penumbral tissue to the final infarction 8 9. Although in these studies the penumbra was defined visually without the use of quantitative thresholds, which may be prone to errors,31 our data point to a differential early response that may progress along the distinct trajectory they illustrate.…”
Section: Discussionmentioning
confidence: 50%
“…While animal models have substantiated the view that tissue response may be distinct with increasing age,6 7 studying this issue in the clinical setting is difficult and has been rarely addressed. Previous work using perfusion–diffusion MRI has suggested that age is a predictor of conversion of penumbral tissue to the final infarction 8 9. These important studies, however, do not describe ischaemic tissue characteristics with concomitant vascular and haemodynamic changes within the acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…Key factors associated with acute ischemic core expansion include the time from symptom onset, 4 collateral status, 6 and site of arterial occlusion. There is mounting evidence that sex and extent of leukoaraiosis (LA) may significantly alter cerebrovascular reserve, 710 which translates to greater infarct growth in animal stroke models. 11,12 Only two respective MRI-based volumetric analyses reported that sex 7 and LA 9 were associated with the expansion of the acute ischemic lesion.…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that sex and extent of leukoaraiosis (LA) may significantly alter cerebrovascular reserve, 710 which translates to greater infarct growth in animal stroke models. 11,12 Only two respective MRI-based volumetric analyses reported that sex 7 and LA 9 were associated with the expansion of the acute ischemic lesion. However, the potential contribution of collaterals and site of arterial occlusion location was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of 141 consecutive AIS patients reveals an interaction between gender and age (17). The median percentage mismatch lost is 7% (0% to 12%) in women and 18% (1% to 35%) in men younger than the population median (71 years, p=0.061).…”
Section: Discussionmentioning
confidence: 97%